Smoking Behavior and Workplace Health Promotion Among Municipal Employees: A Study of Greater Amman Municipality Staff in Jordan - Nour Salah Abdeljawad; Shtoura Aladwan; Yasar Alkhitan (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
This study explores how common smoking is among employees of the Greater Amman Municipality (GAM) in Jordan. It looks at patterns and reasons behind smoking within the context of both national and global efforts to create smoke-free public spaces. We used a cross-sectional design and a structured electronic questionnaire to gather data on tobacco use, demographics, job stress, quitting behavior, and knowledge of available support services. The results show that 36% of GAM employees smoke, with traditional cigarette use being the most common type. Smoking behavior is notably linked to factors like how long employees have worked there, their stress levels, and how young they started smoking. Although 53% of smokers tried to quit, only 32% of those who knew about cessation clinics actually used them. Almost 70% of respondents reported being exposed to second-hand smoke, even though 66% thought GAM was a smoke-free environment. These findings emphasize how workplace culture, psychological stress, and gaps in enforcement contribute to ongoing smoking habits. The study highlights the urgent need for health promotion strategies that include support for quitting, mental health resources, and effective policy actions focused on municipal workers. It adds to the existing literature on occupational health in urban areas of the Middle East and backs national tobacco control efforts aimed at cutting down smoking in public sector workplaces.